AccomodaUve esotropia combined-type. A case report - Wasisdi Gunawan Wasisdi Gunawan (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1996)
A 10 year old girl suffering from esotropia for distant vision since she was 4 years old has been reported. Distant correction of S+3 to S + 4 dioptries resulted in orthophoric eye whereas esotropia still developed during the close work. By adding S+3 dioptries for close work this esotropia disappeared. Until now the patient has been using bifocals with comfort. Accommodative esotropia is a type of esotropia accommodative factor. This condition can be caused by hypermetropic refractive anomaly alone so that it is called refractive accommodative esotropia. Consequently corrective measure of underlying refractive errors will correct the eye deviation. Meanwhile esotropia that manifests during the accommodation alone, such as In close work and not due to refractive error is called non refractive accommodative esotropia. This type of esotropla is due to a higher AC/A ratio. Accommodative esotropia combined type is a combination of these two types of esotropia mentioned above. In this type, esotropia still occurs in close work (accommodation) although its refractive anomaly has been corrected. In this case, addition of positive lens 2-3 dioptries for close work (near vision) will cure this accommodative esotropia. The patient needs a bifocals.Key words : accommodative esotropia - non accommodative esotropia - AC/A ratio - distant correction - addition for close work.